Joint Sequence Learning and Cross-Modality Convolution for 3D Biomedical Segmentation - Kuan-Lun Tseng; Yen-Liang Lin; Hsu, Winston; Chung-Yang Huang (2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2017)
Deep learning models such as convolutional neural network have been widely used in 3D biomedical segmentation and achieve state-of-the-art performance. However, most of them often adapt a single modality or stack multiple modalities as different input channels, which ignores the correlations among them. To leverage the multi-modalities, we propose a deep convolution encoder-decoder structure with fusion layers to incorporate different modalities of MRI data. In addition, we exploit convolutional LSTM (convLSTM) to model a sequence of 2D slices, and jointly learn the multi-modalities and convLSTM in an end-to-end manner. To avoid converging to the certain labels, we adopt a re-weighting scheme and two phase training to handle the label imbalance. Experimental results on BRATS-2015 [13] show that our method outperforms state-of-the-art biomedical segmentation approaches.